Alcohol, addiction and Christian ethics - Cook, Chris (Christopher C.H.) (New studies in Christian ethics, 2006)
Academic perspectives on addictive behaviour usually come from clinical and scientific standpoints, rejecting the 'moral model'. Cook reassesses the nature of addiction and considers the ethical challenges presented by alcohol use and misuse to both individuals and society, arguing that theology should not be excluded from serious discourse about addiction.